1990
DOI: 10.2466/pms.1990.71.3.832
|View full text |Cite
|
Sign up to set email alerts
|

Changes of Eye-Blink Activities during Hypnotic State

Abstract: Three experiments were conducted to examine eye-blink activity during the hypnotic state. The results were as follows: (1) eye-blink rate was dramatically reduced during the hypnotic as compared to the nonhypnotic state, (2) blink-rate variability between events (for example, the task and rest period) was smaller under the hypnotic than under the nonhypnotic state, (3) decrements, after induction of hypnosis, were observed in all aspects of blink-wave attributes (amplitude, duration, slope, and area). These fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…This study further explored the findings of Weitzenhoffer (1969) and Tada et al (1990) that eyeblink frequency is related to hypnotic susceptibility and hypnotic state. Across all conditions, the difference between high-and lowsusceptible subjects is quite striking; in fact, this main effect accounted for almost a l l of the variance.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…This study further explored the findings of Weitzenhoffer (1969) and Tada et al (1990) that eyeblink frequency is related to hypnotic susceptibility and hypnotic state. Across all conditions, the difference between high-and lowsusceptible subjects is quite striking; in fact, this main effect accounted for almost a l l of the variance.…”
Section: Discussionmentioning
confidence: 88%
“…The high-susceptible subjects showed a 66% decrease in blink rate from a baseline reading. More recently, Tada, Yamada, and Hariu (1990) reported a series of studies suggesting that blink rate was dramatically reduced during the hypnotic state, as well as finding a relationship between high susceptibility and decreased blink rate. Although these studies tend to support Weitzenhoffer's (1969) research, they are poorly controlled and report no quantitative data.…”
Section: Hypnotic Susceptibility and The Endogenous Eyeblink: A Briefmentioning
confidence: 96%
“…A later study (Tada, Yamada, & Hariu, 1990) confirmed the decrease in blink rate during hypnosis but also disregarded the blink rate while not in a hypnotic state. Lindsay, Kurtz, and Stern (1993) investigated specifically the blink rate before as well as during hypnosis and, contrary to our expectations, found an increased rate for low hypnotizables.…”
mentioning
confidence: 80%
“…Consequently, in our hypothesis, MCS patients could have more widespread residual cortical functions than VS patients to sustain it. However, it is not overall correct to consider the visual blink exclusively linked to subcortical structures because it could be in part modulated by cortex or cerebellum as reported in some articles (Liu & Ronthal, 1992; Tada, Yamada, & Hariu, 1990) although it is certainly possible to imagine the preservation of the blink even in patients with more extensive cortical damage. In this sense, our study aims to focus on the visual system of patients with DoC trying to find “where” were the main differences between the two groups.…”
Section: Discussionmentioning
confidence: 99%